IMPLEMENTASI MUSYARAKAH SEBAGAI PEMBIAYAAN UMKM DI KECAMATAN CIBIRU KABUPATEN BANDUNG - Arif Lukmanul Hakim; Abdul Faqih; Sandy Pratama (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, contributing significantly to the Gross Domestic Product (GDP) and employment. However, access to financing remains a major constraint. The musyarakah contract as a sharia-based financing scheme offers a solution grounded in justice, transparency, and profit-sharing. This model is relevant for implementation as it aligns with sharia principles and supports collaborative and sustainable business growth. This study employs a qualitative approach with a descriptive-analytical method to understand the implementation of the musyarakah contract among MSMEs in Cibiru District. Data were collected through in-depth interviews and observation, then analyzed using an interactive model encompassing data collection, sorting, presentation, and conclusion drawing. The research focuses on understanding, practices, and the impact of musyarakah on MSME actors. The application of musyarakah has brought positive impacts for MSMEs, increasing income, expanding partnerships, and broadening business operations. MSME actors comprehend the principles of profit-sharing, justice, and transparency, although the level of technical understanding varies. Musyarakah is considered more flexible compared to fixed-interest systems and is capable of fostering collaboration, risk-sharing, and supporting business expansion based on sharia values. Musyarakah has proven effective as an MSME financing scheme by enhancing income and strengthening business partnerships. The profit-sharing system is deemed fair, flexible, and sharia-compliant. While business actors' understanding varies, the values of transparency and honesty remain evident. Strengthening literacy, mentoring, and developing inclusive musyarakah products is essential to support more optimal and sustainable implementation.